Mantle cooling regulation and ancient geomagnetic field - Reshetnyak Maxim (Russian Journal of Earth Sciences, 2022)
The joined core and mantle thermal evolution model of the Earth for 6 Gy is considered. The model describes evolution of the heat fluxes, temperature distribution in the Earth, energy available for the magnetic field generation. Using Monte Carlo method we find parameters of the model which produce realistic inner core size, heat flux at the surface of the planet, viscosity and temperature of the mantle. The quite large heat flux at the core-mantle boundary and corresponding energy source for geodynamo after accretion help to explain existence of the ancient geomagnetic field before the inner core origin.